Artificial Non-intelligence and Anti-money Laundering - Demetis, Dionysios S. (Niesztuczna inteligencja i przeciwdziałanie praniu pieniędzy, 2010)
This paper deals with the popular belief that a technological solution for the domain of money laundering is possible; the paper takes an opposing view by examining some of the complexities underpinning the modelling of the problem domain and postulates some general systemic properties that are acting against any concept of "solution". While a number of computational techniques have been advanced for the profiling of money laundering behaviour, the algorithmic representations behind the queries cannot effectively reduce the complexity of the phenomenon. While these approaches are useful for financial institutions that wish to demonstrate compliance, they fall short of expectations. Complex human behaviour cannot be easily modelled and the intrinsic risk in any act of computational categorization is passed on as yet another layer of complexity.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 104, s. 194-203
Keywords: money laundering; profiling; technology; risk; systems theory